Crypto Currency and its Susceptibility to Speculative Bubbles, Manipulation, Scams and Fraud - BARNES, Paul (Journal of Advanced Studies in Finance, 2019)
It is argued here that because a cryptocurrency has no intrinsic value, problems relating to day-to-day valuation and pricing arise. It is shown how these lead to the reversal of the conventional relationship between supply and demand and the susceptibility of the cryptocurrency markets to irrationality and speculative bubbles arising from the herding instinct. Also, as the cryptocurrency markets are largely free of regulation and the desire for privacy by founders, owners and developers is so great, accountability and disclosure requirements are either minimal or non-existent, leading to the manipulation of cryptocurrency prices, volume and market capitalisation information. Another consequence of their freedom from regulation, particularly surprising given the importance placed on their security through the use of blockchain, is the magnitude of thefts of cryptocurrency (both in terms of frequency and size) levels of which would neither be expected nor tolerated in regulated financial markets.